PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL INTERVENING PADA PT. PRIMATAMA MULIA JAYA (PMJ) IV KOTO KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Hariri, Fardinal Rafiq; Sari, Vivi Nila; Pratiwi, Nila (Journal of Information System, Applied, Management, Accounting and Research, 2024)
This research aims to determine and attempt to analyze the influence of the work environment and work stress on employee performance with employee job satisfaction as an intervening variable at PT. Primatama Mulia Jaya (PMJ) IV Koto, Kinali District, West Pasaman Regency. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research are employees of PT. Bhakti Valley Plantation. The research results found that there is an influence between the work environment and employee job satisfaction. There is no influence between Job Stress and Employee Job Satisfaction. There is no influence between the Work Environment and Employee Performance. There is no influence between Job Stress on Employee Performance. There is an influence between Employee Job Satisfaction on Employee Performance. Employee Job Satisfaction mediates the Work Environment on Employee Performance. Employee Job Satisfaction does not mediate Job Stress on Employee Performance.